Pengaruh Kecepatan Landing dan Pemilihan Material terhadap Faktor Keamanan Landing Skid Helikopter Tanpa Awak Menggunakan Ansys Workbench - Lasinta Ari Nendra Wibawa (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2021)
Landing skids are an important component of uncrewed helicopters. The landing skid acts as a support when the helicopter lands or is parked. This paper examines the effect of landing speed and material selection on the safety factor of uncrewed helicopter landing skids using Ansys Workbench. The uncrewed helicopter weighs 100 kg and an impact time of 0.5 seconds. Landing speed variations are 2 m/s, 3 m/s, and 4 m/s. The materials used in the simulation are plastic types, namely ABS, HDPE, Polyamide (PA6), and Polycarbonate (PC). The simulation results show that the ABS and HDPE materials can only withstand impact loads up to a landing speed of 3 m/s because they have a safety factor of 3.57 and 3.69, respectively. Meanwhile, Polyamide (PA6) and Polycarbonate (PC) can withstand impact loads up to a landing speed of 4 m/s because they have a safety factor of 4.19 and 6.03, respectively